Pengaruh Consumer Ethnocentrism, Religious Animosity Terhadap Boycott dengan Brand Loyalty Sebagai Variabel Intervening pada Konsumen McDonald’s di Semarang (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of Consumer Ethnocentrism and Religious Animosity on Boycott behavior, with Brand Loyalty as an intervening variable, among McDonald’s consumers in Semarang City. The boycott phenomenon against foreign brands, including McDonald’s, is driven by increasing religious and nationalistic sentiments among consumers. This research employs a quantitative approach with an explanatory research design. The sample consists of 100 respondents selected using a purposive sampling technique. Data were analyzed using the Structural Equation Modeling (SEM) method with SmartPLS 4 software. The results show that Brand Loyalty has a significant positive effect on Boycott. Religious Animosity has a significant negative effect on Brand Loyalty. Consumer Ethnocentrism does not directly affect Boycott but has an indirect effect through Brand Loyalty. These findings indicate that brand loyalty can serve as a bridge in the relationship between ethnocentric attitudes and boycott intentions, while also enhancing the understanding of consumer behavior amid ideological and religious conflicts